117k views
5 votes
3(x² - 4y + x) when x = 6 and y = 7

User Drakarah
by
5.4k points

2 Answers

7 votes
Given question ,


3 (x^(2) - 4y+x)

Also , x = 6 and y = 7

Substituting , we get ,


3( 6^(2) - 4(7) + 6)

=> 3 (36-28 + 6)

=> 3(14)

=> 42
User Dmitriy  Korobkov
by
5.2k points
3 votes

Answer:

42

Explanation:

3(6^2-4*7+6)

6^2=36

4*7=28

(36-28+6)=14

3(14)=42

User Caleb Gates
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.